Multi-Spectroscopic and Molecular Simulation Approaches to Characterize the Intercalation Binding of 1-Naphthaleneacetic Acid With Calf Thymus DNA - Hu, Xing; Luo, Xiaoqiao; Zhou, Zhisheng; Wang, Rui; Hu, Yaqin; Zhang, Guimei; Zhang, Guowen (Frontiers in Toxicology, 2021)
1–Naphthaleneacetic acid (NAA), having high-quality biological activity and great yield-increasing potential in agricultural production, is a broad-spectrum plant growth regulator. Although NAA is of low toxicity, it can affect the balance of the human metabolism and damage the body if it is used in high quantity for a long time. In this study, the interaction of NAA with calf thymus DNA (ctDNA) was investigated under simulated human physiological acidity (pH 7.4) using fluorescence, ultraviolet-visible absorption, and circular dichroism spectroscopy combined with viscosity measurements and molecular simulation techniques. The quenching of the endogenous fluorescence of NAA by ctDNA, observed in the fluorescence spectrum experiment, was a mixed quenching process that mainly resulted from the formation of the NAA–ctDNA complex. NAA mainly interacted with ctDNA through hydrophobic interaction, and the binding constant and quenching constant at room temperature (298 K) were 0.60 × 105 L mol−1 and 1.58 × 104 L mol−1, respectively. Moreover, the intercalation mode between NAA and ctDNA was verified in the analysis of melting point, KI measurements, and the viscosity of ctDNA. The results were confirmed by molecular simulation, and it showed that NAA was enriched near the C–G base of ctDNA. As shown in circular dichroism spectra, the positive peak intensity of ctDNA intensified along with a certain degree of redshift, while the negative peak intensity decreased after binding with NAA, suggesting that the binding of NAA induced the transformation of the secondary structure of ctDNA from B-form to A-form. These researches will help to understand the hazards of NAA to the human body more comprehensively and concretely, to better guide the use of NAA in industry and agriculture.